Optimization of the chromatographic behaviors of quercetin using choline chloride-based deep eutectic solvents as HPLC mobile-phase additives. Issue 2 (22nd January 2018) - Gao, Fan; Liu, Lingling; Tang, Weiyang; Row, Kyung Ho; Zhu, Tao
ABSTRACT: Nine types of deep eutectic solvents (DESs) were used as mobile-phase additives to improve the chromatographic behaviors of quercetin. Three variables (temperature, molar ratio and concentration) were studied. According to the ion interaction theory and the hydrogen bond, DESs components can work as ions and play an ion-pairing role with quercetin at the same time. Under the optimum condition, the number of theoretical plates was 6690.8 and the tailing factor was 1.71. Compared with acetic acid (HAc), DESs as mobile-phase additives would not damage the High Performance Liquid Chromatography (HPLC) system. The excellent properties of DESs showed their potential as additives for the determination of quercetin.